Analysis of spatial-temporal evolution and influencing factors of carbon emission efficiency in Chinese cities - Huang, Hui; Wei, Zhaoxi; Ge, Qingru; Guo, Qingjie (Frontiers in Environmental Science, 2023)
Improving carbon emission efficiency and reducing carbon emissions is crucial to achieving the goal of carbon neutrality and carbon peak. This paper focuses on 278 cities in China from 2000 to 2017, and uses the undesired output SBM model to measure the carbon emission efficiency of each city. The results showed that during the research period the average carbon emission efficiency of China gradually dropped from 0.6 to 0.5. After classifying the carbon emission efficiency of each city. The number of cities in 2005 belonging to high-efficiency areas decreased by 11.76 % compared with 2000. From 2005 to 2010, the number of cities in the medium-low-efficiency areas and low-efficiency areas increased from 122 to 143. It is found that the spatial-temporal evolution of carbon emission efficiency, on the whole follows a certain evolution law and has spatial auto-correlation. In addition, the SDM model is selected to explore the influencing factors of urban carbon emission efficiency. The findings demonstrate that optimizing the quality of urban development, improving the ability of scientific, and technological innovation, grasping government intervention, and encouraging the introduction of high-quality foreign capital will play a positive role in improving the low efficiency of carbon emissions in cities.